TEKNOLOGI DIGITAL INOVATIF DALAM APARTEMEN PINTAR : MEMENUHI KEBUTUHAN ORANG LANJUT USIA DAN PENYANDANG DISABILITAS - Tanuwidjaja, Gunawan; Rustanto, Jessica Louise; Adeline; Kelly; Hartanto, Fiona Claudia (Seminar Nasional Ilmu Terapan, 2024)
Integration of digital technology in smart apartment design is crucial to meet the needs of the elderly and people with disabilities. As life expectancy increases, architects face the challenge of designing homes that adhere to universal design principles, including accessibility, safety, comfort, and independence for residents experiencing physical decline, such as hearing, vision, or mobility impairments. In this context, multidisciplinary collaboration is essential to drive behavioral change and create a sustainable future through inclusive design. Research on the MS Queensland Caboolture Apartments in Queensland, Australia, highlights the importance of inclusive and accessible housing for people with disabilities. These apartments, part of the Orion on Rowe community, are designed with features like ramps, wide doors, and smart hometechnology to enhance the independence and comfort of their residents. The research findings indicate that these apartments have successfully improved the quality of life for their residents, with 77% reporting increased well-being. This underscores the importance of design that considers special needs in modern architecture, creating homes that are not only comfortablebut also support the independence and well-being of the occupants.